A new double procedure Palliative Bypass in Periampullary Cancer - Colet, Andrés; Berhouet, Horacio; Juambeltz, Nelson; Segura, Daisy; Rodríguez, Gustavo; Praderi, Raúl (Cirugía del Uruguay, 1992)
lncidence of cancer of the pancreas has risen in the /ast ten years. In this period results of cephalic operation can only be performed in /ess than 30% of the patients, there remains a great percentage of pat1ents for palliative treatment. lt must so/ve bi/iary dmin_age by means of a good termino-lateral hepatlco-¡e¡unal anastomosis on a hea/thy biliary stump abandoning the /ower end of the choledochus over the tumor.